Design and synthesis of new dihydropyrimidine/sulphonamide hybrids as promising anti-inflammatory agents via dual mPGES-1/5-LOX inhibition - Al-Wahaibi, Lamya H.; Elshamsy, Ali M.; Ali, Taha F. S.; Youssif, Bahaa G. M.; Bräse, S.; Abdel-Aziz, Mohamed; El-Koussi, Nawal A. (Frontiers in Chemistry, 2024)
A novel series of dihydropyrimidine/sulphonamide hybrids 3a–j with anti-inflammatory properties have been developed and tested as dual mPGES-1/5-LOX inhibitors. In vitro assay, results showed that compounds 3c, 3e, 3h, and 3j were the most effective dual inhibitors of mPGES-1 and 5-LOX activities. Compound 3j was the most potent dual inhibitor with IC50 values of 0.92 µM and 1.98 µM, respectively. In vivo, anti-inflammatory studies demonstrated that compounds 3c, 3e, 3h, and 3e had considerable anti-inflammatory activity, with EI% ranging from 29% to 71%. Compounds 3e and 3j were equivalent to celecoxib after the first hour but exhibited stronger anti-inflammatory effects than celecoxib after the third and fifth hours. Moreover, compounds 3e and 3j significantly reduced the levels of pro-inflammatory cytokines (PGE2, TNF-α, and IL-6) with gastrointestinal safety profiles. Molecular docking simulations explored the most potent derivatives’ binding affinities and interaction patterns within mPGES-1 and 5-LOX active sites. This study disclosed that compound 3j is a promising anti-inflammatory lead with dual mPGES-1/5-LOX inhibition that deserves further preclinical investigation.